(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study explores the role of advanced assessment technology in evaluating teaching and learning styles in Physical Education. Bachelor of Physical Education (BPEd) students were selected as the focus, given their exposure to modern technologies, while teachers often lack the technical expertise necessary to integrate these tools effectively. This gap may contribute to students losing interest in Physical Education. The study aims to bridge theory and practice by equipping students with the knowledge, skills, and mindset needed to adapt to the evolving educational landscape. A proposed intervention plan will address specific challenges by fostering digital literacy, encouraging evidence-based decision-making, and promoting innovation. Targeted initiatives such as workshops, seminars, hands-on training, and collaborative projects will empower students to effectively utilize advanced assessment technology in both academic and professional settings. The researchers employed a probability sampling method to collect data on current trends in advanced assessment technology, serving as the foundation for a proposed intervention plan. The findings were thematically analyzed to highlight key insights. A simple random sampling technique was used to ensure an unbiased selection of respondents. Data collection was conducted through survey questionnaires and checklists, which were distributed digitally via Google Forms. These findings underscore the importance of considering gender-specific differences when addressing challenges and leveraging technology to enhance teaching and learning experiences for BPEd students. Further research is needed to develop tailored interventions that effectively meet the unique needs of both male and female students. The research findings reveal widespread acceptance of technology in assessments while highlighting distinct gender-based engagement patterns. Males demonstrate greater motivation in cognitive tasks, particularly memory-based assessments, indicating a preference for technology-driven learning. Meanwhile, females show stronger engagement in socio-emotional aspects, suggesting that technology can be effectively utilized to support both cognitive and emotional development, fostering a more holistic learning experience.